Learners' motivation and the language learning strategies (LLS) used by Iraqi EFL preparatory learners in the English context - Ali, Nadhim (Science Research Society, 2021)
This study investigates the language learning strategies (LLS) used by Iraqi EFL learners in preparatory schools. The growing interest in learning strategies has increased the need for learning English as a foreign language in terms of two essential variables: strategy use and motivation. Oxford SILL (1990) was used to analyse effective learning strategies employed in learning activities. The results of one-way analysis of variance (ANOVA) show that memory learning strategies have the highest mean score (M= 4.06, SD=.394 ). In contrast, affective learning strategies have the lowest mean score (M= 2.48, SD=.837). Furthermore, the results suggest that the MSLQ's motivational subscales are substantially linked with various strategies of SILL. Pearson's Chi-Square value for MSLQ and SILL indicates a significant positive correlation of r (.820) =.003, which is less than the 0.05 level of significance. As a result, the Pearson Correlation Coefficients show that learners' motivation affects their learning strategies for success. The substantial relationship between motivation and LLS in classroom activities was linked to EFL learners' achievement in learning English as a foreign language. The study suggests that EFL learners should use numerous learning strategies to build their learning skills successfully. Besides, a teacher must employ numerous motivational techniques to facilitate English learning process and improve learners' English language skills effectively.